Arvi Grotenfelt and neo-Kantian philosophy of history - Kallio, Lauri (Con-Textos Kantianos. International Journal of Philosophy, 2020)
The paper discusses Arvi Grotenfelt's (1863–1941), professor of philosophy in Helsinki 1905–29, reading of Heinrich Rickert's (1863–1936) philosophy of history. Rickert was one of the key figures of the so-called south-west German neo-Kantianism. In the center of attention of the south- west neo-Kantians was the topic that Immanuel Kant (1724–1804) himself had omitted: how to philosophically establish the humanities and the social sciences and separate them from the natural sciences? Rickert's philosophy of history was essentially an attempt to ground the historical knowledge in a strictly transcendental philosophy in the Kantian sense. His argumentation relied on his concept of value (Wert). Grotenfelt did not share Rickert's definition of values. According to his view, the fundamental foundation of our judgements of value is beyond scientific reasoning. I will also argue that Grotenfelt's standpoint has a general affinity to Wilhelm Dilthey's (1833–1911) philosophy of world view (Weltanschauung).